2015
DOI: 10.1007/s40843-015-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-doped semiconductor nanocrystals: electronic structures and optical properties

Abstract: solid state lightings [11,12]. Nevertheless, due to the parity forbidden transition nature, the absorption cross-section of f-f transition is small and usually high power light sources such as laser are needed to excite the Ln 3+ ions. The ability to excite Ln 3+ ions efficiently in a broad spectral range is strongly desired for realizing their full potentials in signaling and lighting applications. To improve the excitation efficiency of Ln 3+ , sensitization is an efficient way to avoid the direct excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 210 publications
0
50
0
Order By: Relevance
“…A significant improvement in ET from the semiconductor nanocrystals (SNC) has led to an efficiently sensitized UCL emission. Meanwhile, the inefficient absorptions of the forbidden 4f-4f transitions of Ln ions have been overcome [27]. With the doped (Eu 3+ )Y 2 O 3 nanocrystals, it was reported that the UCL intensity of SNC was enhanced via the ET from the excited host to the Eu 3+ ions [28].…”
Section: Introductionmentioning
confidence: 99%
“…A significant improvement in ET from the semiconductor nanocrystals (SNC) has led to an efficiently sensitized UCL emission. Meanwhile, the inefficient absorptions of the forbidden 4f-4f transitions of Ln ions have been overcome [27]. With the doped (Eu 3+ )Y 2 O 3 nanocrystals, it was reported that the UCL intensity of SNC was enhanced via the ET from the excited host to the Eu 3+ ions [28].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Thep ast decade has witnessed the tremendous development of luminescent nanoprobes based on trivalent lanthanide doped nanocrystals (Ln 3+ -NCs) due to the unique electronic structures and optical properties of Ln 3+ emitters. [2] Through the sequential absorption of two or more nearinfrared (NIR) photons,L n 3+ -NCs can emit visible upconversion luminescence (UCL) and down-shifting luminescence (DSL) in the second NIR window (NIR-II, 1000-1700 nm) to markedly eliminate autofluorescence signals and light scattering from biological molecules/tissues, [3] resulting in greatly improved light penetration depth and signal-to-noise ratio (SNR) in bioimaging. [4] Moreover,L n 3+ -NCs have tunable luminescence wavelengths and lifetimes by properly doping Ln 3+ or designing core-shell structures,w hich opens new avenues for multiplex imaging through color and lifetime encoding.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Thep ast decade has witnessed the tremendous development of luminescent nanoprobes based on trivalent lanthanide doped nanocrystals (Ln 3+ -NCs) due to the unique electronic structures and optical properties of Ln 3+ emitters. [2] Through the sequential absorption of two or more nearinfrared (NIR) photons,L n 3+ -NCs can emit visible upconversion luminescence (UCL) and down-shifting luminescence (DSL) in the second NIR window (NIR-II, 1000-1700 nm) to markedly eliminate autofluorescence signals and light scattering from biological molecules/tissues, [3] resulting in greatly improved light penetration depth and signal-to-noise ratio (SNR) in bioimaging. [4] Moreover,L n 3+ -NCs have tunable luminescence wavelengths and lifetimes by properly doping Ln 3+ or designing core-shell structures,w hich opens new avenues for multiplex imaging through color and lifetime encoding.…”
Section: Introductionmentioning
confidence: 99%